100 articles evaluated by IJAME and JMES - Shalfarina, Shahriman (Penerbit UMP, 2015)
Kuantan- A total of 100 articles were evaluated by the International Journal of Automotive and Mechanical Engineering (IJAME) and Journal of Mechanical Engineering and Sciences (JMES) editorial teams during UMP SCOPUS Journal Evaluation Workshop that was held for three days at Suria Cherating Beach Resort here recently. The workshop was jointly organised by UMP Publisher, Faculty of Mechanical Engineering (FKM) and Training and Competency Development Division (BLPK).